Diagnosis and Management of the Overlap Syndromes of Autoimmune Hepatitis - Albert J Czaja (Canadian Journal of Gastroenterology)
BACKGROUND: Autoimmune hepatitis may have cholestatic features that are outside the classical phenotype and that resemble findings in other immune-mediated liver diseases. These cholestatic phenotypes have been designated ‘overlap syndromes’.